2017
DOI: 10.1186/s12974-017-1023-2
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cytokine patterns may regulate the severity of neonatal asphyxia—an observational study

Abstract: BackgroundNeuroinflammation and a systemic inflammatory reaction are important features of perinatal asphyxia. Neuroinflammation may have dual aspects being a hindrance, but also a significant help in the recovery of the CNS. We aimed to assess intracellular cytokine levels of T-lymphocytes and plasma cytokine levels in moderate and severe asphyxia in order to identify players of the inflammatory response that may influence patient outcome.MethodsWe analyzed the data of 28 term neonates requiring moderate syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 86 publications
2
17
1
3
Order By: Relevance
“…Elevated circulating levels of IL-1β are associated with impaired cerebral oxidative metabolism [18] and EEG suppression in neonates [45]. Similarly, in the present study we observed suppression of EEG power and nuchal EMG activity (re ecting reduced neural activity and fetal movement, respectively) after the rst LPS infusion, and sustained reductions in neural activity and fetal movement during the recovery period.…”
Section: Discussionsupporting
confidence: 84%
“…Elevated circulating levels of IL-1β are associated with impaired cerebral oxidative metabolism [18] and EEG suppression in neonates [45]. Similarly, in the present study we observed suppression of EEG power and nuchal EMG activity (re ecting reduced neural activity and fetal movement, respectively) after the rst LPS infusion, and sustained reductions in neural activity and fetal movement during the recovery period.…”
Section: Discussionsupporting
confidence: 84%
“…We found no differences between NAIS and HIE in the intracellular production of IL-1β and TNF-α in CD4 or CD8 cells; however, these cytokines appear to be important in differentiating between the mild and severe form of HIE [41].…”
Section: Intracellular Cytokine Datacontrasting
confidence: 74%
“…The severe group (n = 11) was formed of newborns with moderate-to-severe HIE signs on the MRI scan AND burst-suppression or continuous extremely low voltage or flat tracing background activity on aEEG OR normalization of aEEG after the 48th hour of life or never, OR early death (< 28 days). Neonates that met none of the above-listed criteria constituted the moderate group (n = 17) (mild HIE signs on MRI scans AND continuous or discontinuous normal voltage background activity on aEEG OR normalization of aEEG activity before the 48th hour of life) [41]. Pooled data from the cohort of four NAIS patients were compared to infants with HIE.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular cytokine levels, which closely reflect cytokine production at a cellular level and show more stable kinetics in time, have recently been analyzed in term infants requiring systemic hypothermia after perinatal asphyxia [ 27 ]. In that study, intracellular IL-6 levels in CD4+ peripheral blood mononuclear cells peaked at 24 h post-asphyxia.…”
Section: Discussionmentioning
confidence: 99%